A COMPREHENSIVE LAYERS OF PROTECTION ANALYSIS (LOPA) OF AMMONIA EXPOSURE IN HYBRID OCEAN THERMAL ENERGY CONVERSION (H-OTEC) SYSTEMS (Journal of Energy and Safety Technology (JEST), 2025)
Ocean Thermal Energy Conversion (OTEC) (Figure 1) harnesses the temperature difference between warm surface seawater and cold deep seawater to generate renewable energy. This innovative technology relies on ammonia as a working fluid in closed-cycle systems, where its favourable thermodynamic properties enable efficient energy transfer. However, ammonia usage introduces significant hazards, necessitating comprehensive risk evaluation and mitigation strategies to ensure safe and sustainable operations. Ammonia poses risks to personnel and the environment due to its toxic and corrosive nature. Exposure can result in respiratory distress, eye irritation, or severe health consequences, while accidental releases may lead to water contamination and ecological damage. Common scenarios for ammonia hazards in OTEC systems include leaks from piping or storage tanks, safety valve failures, operator errors, and structural damage from extreme weather. These events have immediate consequences such as injury or environmental harm, as well as long-term impacts, including reputational damage and operational disruptions. These risks, the Layers of Protection Analysis (LOPA) methodology provides a structured framework to identify cause-consequence pathways and evaluate the adequacy of safeguards. Current protective layers include corrosion-resistant materials, ammonia detection systems, safety valves, regular maintenance, and operator training. Additional measures, such as real-time leak detection, automated shutoff systems, predictive maintenance using AI, and enhanced secondary containment, further strengthen system resilience. By systematically assessing risks and implementing robust safeguards, OTEC systems can achieve operational safety, environmental compliance, and long-term reliability, advancing the adoption of this promising renewable energy technology.
Keywords: Ocean Thermal energy Conversion (OTEC); Layers of Protection Analysis (LOPA); Renewal Energy; Hazards; Safeguards